Community-Acquired MRSA Pyomyositis: Case Report and Review of the Literature - Douglas P. Olson; Sarita Soares; Sandhya V. Kanade (Journal of Tropical Medicine)
Community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) is responsible for a broad range of infections. We report the case of a 46-year-old gentleman with a history of untreated, uncomplicated Hepatitis C who presented with a 2-month history of back pain and was found to have abscesses in his psoas and right paraspinal muscles with subsequent lumbar spine osteomyelitis. Despite drainage and appropriate antibiotic management the patient's clinical condition deteriorated and he developed new upper extremity weakness and sensory deficits on physical exam. Repeat imaging showed new, severe compression of the spinal cord and cauda equina from C1 to the sacrum by a spinal epidural abscess. After surgical intervention and continued medical therapy, the patient recovered completely. This case illustrates a case of CA-MRSA pyomyositis that progressed to lumbar osteomyelitis and a spinal epidural abscess extending the entire length of the spinal canal.